2014
DOI: 10.18551/rjoas.2014-12.02
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rainfall Data to Estimate Rain Contribution Towards Crop Water Requirement Using Cropwat Model

Abstract: A study was carried out to define the analysis of rainfall data in order to estimate its contribution towards crop water requirements to overcome these problems. Rainfall and climatic data was collected from metrological stations, C.P UAF rain gauge (A), (AARI), (B), (CAA), (C) and (WAPDA), (D), Faisalabad of given region and this data was reserved for cross validation. The test station's (A) rainfall data was subjected to double mass curve technique to check its consistency with respect to other rainfall stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Effective rainfall contributed 33% to 46% of water to the consumptive use requirement of rice between 2005 and 2012. The average contribution of effective rainfall was about 38%, whereas in Faisalabad, Pakistan, rainfall accounted 20 On the other hand, for other parts of Pakistan, rainfall contribution was found to be between the range of 13.03% and 100%, depending on the season and location. 25 In Senegal, it was found that rainfall contributes less than 30% of the evapotranspiration requirement of rice.…”
Section: Existing Water Reservoir Capacitymentioning
confidence: 83%
See 1 more Smart Citation
“…Effective rainfall contributed 33% to 46% of water to the consumptive use requirement of rice between 2005 and 2012. The average contribution of effective rainfall was about 38%, whereas in Faisalabad, Pakistan, rainfall accounted 20 On the other hand, for other parts of Pakistan, rainfall contribution was found to be between the range of 13.03% and 100%, depending on the season and location. 25 In Senegal, it was found that rainfall contributes less than 30% of the evapotranspiration requirement of rice.…”
Section: Existing Water Reservoir Capacitymentioning
confidence: 83%
“…In Faisalabad, Pakistan, study showed that the rainwater contribution for wheat and maize was around 7.5% and 15.5% per year. 20 The study used CROPWAT computer model to determine consumptive use requirement in that region. Wisser et al 21 performed a global scale study on quantifying the significance of water captured by small reservoirs for crop production.…”
Section: Introductionmentioning
confidence: 99%
“…The crop evapotranspiration (ETc), effective rainfall and irrigation water requirement were estimated using CropWat model developed by the Food and Agriculture Organisation (Allen et al, 1998;Bouraima et al, 2015;Amarasinghe et al, 2010;Laghari et al, 2014;Kumari et al, 2017a ). In the model, the whole cotton crop period was divided into four stages of crop periods i.e.…”
Section: Estimation Of Irrigation Water Requirementmentioning
confidence: 99%
“…The crop water requirement (in m 3 /ha) is calculated from the accumulated crop evapo-transpiration (ET c ) measured in mm/day over the complete crop growing period. Many past researchers have used CropWat model to estimate the crop water requirement (Bouraima et al, 2015;Amarasinghe et al, 2010;Laghari et al, 2014;Allen et al, 1998). The evapo-transpiration (ET c ) was calculated by using formula 1:…”
Section: Estimation Of Crop Water Requirementmentioning
confidence: 99%